Objective PET : - Hashemi, Louise (Cambridge University Press, 2003)
Objective PET offers students complete preparation for the Cambridge Preliminary English Test. The course combines solid language development with systematic and thorough exam preparation and practice. The short units give a sense of progress and cover a wide variety of motivating topics relevant to the exam